Comportamento informacional de servidores e colaboradores da Universidade Federal do Ceará no uso do Sistema Eletrônico de Informações (SEI) - Oliveira, Thiago Pinheiro Ramos de (2019)
It’s about the informational behavior of the Information Electronic System (IES), that have been at the Coordination of Administration and Patrimony (CAP), on the Federal University of Ceará (FUC). As a question point, it propounds: how the servers and contributors from CAP, on FUC, behave in the process of searching information provided on the Information Electronic System? It was established, as the general objective, to analyze the informational behavior of the users of the Coordination of Administration and Patrimony, on the Federal University of Ceará, on searching information at the SEI’s environment, according to the Information Search Process (ISP), by Carol Khulthau. We defined as specifics objectives: identify the needs of the servers and contributors that encourage the information searching; describe the information searching mode by means of the Information Search Process (ISP), created by Carol Kuhlthau; and point the servers and contributors’ difficulties using IES. In order to achieve the established purposes, it was composed an exploratory and descriptive research, with quantitative and qualitative character, configuring a case study, whose the researching locus was the Coordination of Administration and Patrimony, with the servers and contributors, SEI users, being research samples. The sample was formed by 22 (twenty-two) servers and 3 (three) contributors. The instrument of data collect was the questionnaire, whose shipping was made by electronic mail. The Content Analysis was used to organization and interpretation of the collected data. Based on the methodological trajectory, we had these results: the servers and contributors’ needs of information are tied down to the intrinsic assignments to the sector that they execute their activities, so as the process related to their functional life. The content of the documents and the databases inserted on IES impel the users to use it on the process of information searching. The stages of this process evolve the beginning, the selection, the exploration, the formulation, the collect and the presentation specified on the ISP. This process brings feelings of optimism, when the servers and contributors find the information that they need, or frustration, in case of they didn’t make it. It was verified that the IES users has abilities to use the system. However, there are difficulties about the icons representation, the research environment and the functions of the profiles available to the contributors. These occasions possibly brings bad feelings that could influence the process of information search. We suggest, as a user training strategy, in order to overcome the present difficulties, the structuring of a basic course with content that include the management of administration public documents and the best practice on the use of the IES. We conclude that when we noticed the information needs, the servers and contributors from CAP was motivated to begin the process of search on IES, passing by the ISP’s stages and domains. In this process, we can notice the difficulties of the users to use the system, doing well on their researches or not.